2012
DOI: 10.1086/666337
|View full text |Cite
|
Sign up to set email alerts
|

Adequate Disinfection of a Split-Septum Needleless Intravascular Connector with a 5-Second Alcohol Scrub

Abstract: A 5-second scrub with a 70% isopropyl alcohol pledget yields adequate disinfection of a split-septum intravascular catheter connector valve under clinical and laboratory conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…It has been suggested that negative-and positive-displacement mechanical needleless IV access devices, because of their complex design, may be susceptible to contamination. [15][16][17][18] In this study, there were significant differences between the needleless IV access devices with regard to microbial ingress following both cleaning schedules. In comparison, in a recent observational study, rates of bloodstream infection were found to remain at zero regardless of whether a neutral-or positive-displacement valve was used.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that negative-and positive-displacement mechanical needleless IV access devices, because of their complex design, may be susceptible to contamination. [15][16][17][18] In this study, there were significant differences between the needleless IV access devices with regard to microbial ingress following both cleaning schedules. In comparison, in a recent observational study, rates of bloodstream infection were found to remain at zero regardless of whether a neutral-or positive-displacement valve was used.…”
Section: Discussionmentioning
confidence: 99%
“…Apply mechanical friction for no less than 5 seconds to reduce contamination. 121,122 It is unclear whether this duration of disinfection can be generalized to needleless connectors not tested in these studies. a.…”
Section: Lowmentioning
confidence: 98%
“…Two additional studies gave conflicting results. Rupp demonstrated 5 second alcohol disinfection was effective; this was in direct contrast with the Smith study where contact time of 10/12/15 seconds was deemed adequate, but 5 and 8 seconds were not as effective to prevent bacterial transfer [170,171]. Simmons and colleagues found 3/10/15 seconds significantly decreased the bacterial load in an in vitro laboratory study, with some level of bacteria remaining during all duration levels tested; disinfection failed to completely eliminate contaminants [13].…”
Section: Disinfection Practicesmentioning
confidence: 81%